Лінгвістичний аналіз філософського дискурсу: питання ідентифікації і характеризації - Малиновська, І.В. (Центр наукових досліджень та викладання іноземних мов НАН України, 2009)
The article discusses a number of difficulties of linguistic identification of philosophical discourse. Considered have been semantic, lexical and grammatical as well as stylistic and structural peculiarities of the modern English discourse of philosophy. The thesis on its double nature being entailed by a unique character of philosophy as both intuitive and objective reasoning has been postulated.